Impact of acute kidney injury after extended liver resections. Issue 7 (July 2021) - Reese, Tim; Kröger, Fabian; Makridis, Georgios; Drexler, Richard; Jusufi, Maximilian; Schneider, Martin; Brüning, Roland; von Rittberg, York; Wagner, Kim C.; Oldhafer, Karl J.
Abstract: Background: Complex liver resection is a risk factor for the development of AKI, which is associated with increased morbidity and mortality. Aim of this study was to assess risk factors for acute kidney injury (AKI) and its impact on outcome for patients undergoing complex liver surgery. Methods: AKI was defined according to the KDIGO criteria. Primary endpoint was the occurrence of AKI after liver resection. Secondary endpoints were complications and mortality. Results: Overall, 146 patients undergoing extended liver resection were included in the study. The incidence of AKI was 21%. The incidence of chronic kidney disease (CKD) and hepatocellular carcinoma were significantly higher in patients with AKI. In the AKI group, the proportion of extended right hepatectomies was the highest (53%), followed by ALPPS (43%). Increased intraoperative blood loss, increased postoperative complications and perioperative mortality was associated with AKI. Besides age and CKD, ALPPS was an independent risk factor for postoperative AKI. A small future liver remnant seemed to increase the risk of AKI in patients undergoing ALPPS. Conclusion: Following extended liver resection, AKI is associated with an increased morbidity and mortality. ALPPS is a major independent risk factor for the development of AKI and a sufficient future liver remnant could avoid postoperative AKI.